Interculturality and communicative competence in medical training: A bet to overcome the language barrier - Carrascal-Fuentes, José Alfredo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Aware of the meaning of the interrelationships, the competence of a native language in primary and hospital care physicians in societies and communities where cultural care pluralism converges is considered relevant, in congruence, to approximate the sociomedical context and the specific institutional and community actors , in order to resignify the doctor-patient relationship from the dialectical authenticity of the autochthonous groups that make it possible to mitigate linguistic disagreements within plural contexts, granting the comprehensive management of the patient and responding to health needs, a complex and challenging practice to recognize ethnic and cultural heterogeneity.